Plasma Systems in Thin Film Technology - A. P. Dostanko; S. I. Madveyko; E. V. Telesh; S. N. Melnikov; S. M. Zavadski; D. A. Golosov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The article discusses the current trends in the development of ion-plasma systems for ion processing and thin film deposition. Application of pulsed reactive magnetron sputtering for deposition of vanadium oxide films and dependence of process parameters on power supply frequency characteristics, peculiarities and application of direct ion-beam deposition for formation of coatings based on SiO2 for optical coatings, SiO2, CH, CN, CHF for orientation coatings of LCD displays, wear-resistant coatings of diamond-like carbon (α-C) and carbon nitride (CNx) are considered. The advantages of continuous microwave magnetron power over pulsed mode are shown. The mathematical model for calculating magnetron sputtering systems, processes of magnetron sputtering and the main capabilities of the developed software complex Deposition are shown.